Research on rules design of human-machine command countermeasure system - REN Pei-zhong, WANG Zhu (Zhihui kongzhi yu fangzhen, 2023)
In view of the shortcomings of the existing human-machine command countermeasure system in the design research of the rules, according to the typical structure of human-machine command countermeasure system and rule reasoning operation mechanism, and the requirements of the rules of human-machine command countermeasure system are proposed. The basic contents and structures of the rules library are designed, and the composition and contents of the elements and contents of the rules library and the command decision rules library are expounded in this paper. For more, some examples are given. Finally, the application of the rule library in the construction of the intelligent countermeasures model is illustrated. The design solution can give other similar kinds of human-machine countermeasure system and rules construction a reference,and it has great operability.